Complement related pattern recognition molecules as markers of short-term mortality in intensive care patients. Issue 4 (April 2020) - Hansen, Cecilie B.; Bayarri-Olmos, Rafael; Kristensen, Markus K.; Pilely, Katrine; Hellemann, Dorthe; Garred, Peter
Highlights: Comprehensive overview of complement related pattern recognition molecules (PRMs) in ICU patients. Time dependent analysis of plasma PRM levels during ICU stay. High PTX3 and CRP levels were independently associated with increased 28-day mortality. A high MBL level was independently associated with improved chance of survival. PTX3 appears to be a superior marker of septic shock compared to CRP. Summary: Objectives: To evaluate the complement related pattern recognition molecules (PRMs) PTX3, MBL, CL-11, ficolin-2 and -3, along with the established marker CRP, to predict 28-day mortality and disease severity of sepsis in patients admitted to the intensive care unit (ICU). Methods: In a single-center, prospective, observational study 547 patients were included over a period of 18 months. Blood samples were obtained at admission to the ICU and the following 4 days. Results: PTX3 baseline levels were significantly higher in non-survivors compared to survivors, whereas MBL and ficolin-2 levels were significantly lower in non-survivors compared to survivors. A PTX3 level above the median was independently associated with 28-day mortality in the adjusted analysis including age, sex, chronic disease and immunosuppression (HR 1.87, 95% CI [1.41–2.48], p  < 0.0001), while a MBL level above the median was associated with increased chance of survival (HR 0.75, 95% CI [0.57–0.98], p  = 0.034). Ficolin-2 was only borderline significant (HR 0.79, 95% CI [0.60–1.03], p  = 0.084). In a ROC analysis PTX3 was superior to CRP in predicting septic shock. Conclusions: PTX3, MBL and CRP levels were independently associated with 28-day mortality in ICU patients. PTX3 was a better marker of septic shock compared to CRP.